On development of spoke plot for circular variables - Hussain, F.; Hussin, A.G.; Zubairi, Y.Z. (Chiang Mai Univ, 2010)
Relationship and simple analysis between two any circular variables are the main focus of this paper. Correlation measure, linear relationship and estimation of concentration parameters are some examples of simple approach in analyzing two circular variables. These analyses could be extended to the graphical plots to give a better understanding. A plot called ``Spoke plot'' which have been developed in MATLAB environments have been proposed to achieve this objective. As an illustration, the application of ``Spoke plot'' as a simple analysis between two circular variables using graphical plots in investigating the correlation, linear relationship and estimating concentration parameters are given using the Malaysian wind direction data.